Determination of Adsorption Potential of Waste Tyre-Based Activated Carbon for Heavy Metal Removal (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Developing countries including Kenya, have recorded rapid growth in industrialization and population. This growth has contributed to a rise in wastewater pollution, leading to serious environmental and health risks. Paint and pigment manufacturing industries release heavy metals like lead, cadmium, and chromium into water bodies. These heavy metals threaten aquatic life and human health. Traditional treatment methods are costly and not widely used, creating a need for sustainable alternatives.This study examines the efficiency of coagulation, flocculation, and adsorption in removing heavy metals from industrial wastewater. Waste tires were carbonised at 700°C to yield activated carbon adsorbents. They were later cleaned and optimised. Coagulation-flocculation with aluminium sulphate reduced turbidity by 45.73-55.26%, however it was insufficient for heavy metal removal. The efficacy of adsorption with tire-derived activated carbon relies on pH, contact time, and adsorbent dose. However, it did not entirely fulfil EMCA criteria, pointing out the need for further enhancements. These studies demonstrate the possibility of repurposing waste materials for environmental cleaning. With further optimisation and large-scale use, tire-based activated carbon could provide a low-cost, long-term option for wastewater treatment. This will help to reduce industrial pollution and protect water sources.